Effects Of Fish Amino Acid (Faa) Application on Growth and Development of Okra (Abelmoschus Esculentus) at Different Sampling Times - Johari, Nor Syakina; Abdul Mutalib, Asila; Ismail, Zalina; Ismail, Fazhana; Ab Latif, Zahidah; Che Man, Shaibatul ' Islamiah; Tang, Jing Rui (Universitas Ahmad Dahlan, 2020)
An experiment was conducted to determine the effects of fish amino acid (FAA) application on growth and development of okra (Abelmoschus esculentus) with different sampling times. It was placed at Soil Science Laboratory, Blok Pakar at the Universiti Pendidikan Sultan Idris (UPSI). The okra plant was treated with a different amount of FAA (5 mL and 10 mL). Total of experimental units were 24. The used experimental design was Randomised Complete Block Design (RCBD). The parameters such as root length, shoot length, plant biomass, soil pH and soil moisture content were analysed after 2 weeks and 4 weeks of transplanting. The data was analysed by using Analysis of Variance (ANOVA), Statistical Package for the Social Sciences (SPSS) and means comparison were using Tukey HSD test with significant level (Pâ‰¤0.05). Results showed that FAA application and different sampling times were significantly affected the shoot length of okra. Besides, the volume of FAA and the number of weeks were significantly affected the soil pH and the soil moisture content, respectively. However, the addition of FAA application did not affect the root length and plant biomass of okra.